(untitled) (Fiep Bulletin - online, 2014)
Objective - to Analyze the life conditions and of the daily relating the practice of physical activity and the quality of employees’ of a provision industry life. He/she took place eleven interviews, where it was verified that the employees try to maintain healthy habits, however, the feeding appeared as the largest difficulty found by them, the level socioeconômico and of instruction they can be decisive of that picture. The daily and the conditions of the employees’ of the provision industry life in subject demonstrate the difficulties found by the population of low income for us to maintain healthy habits. The public politics need to be gone back to that reality.